If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y+7-4y=5
We move all terms to the left:
2y+7-4y-(5)=0
We add all the numbers together, and all the variables
-2y+2=0
We move all terms containing y to the left, all other terms to the right
-2y=-2
y=-2/-2
y=1
| 3+4p-1=-22 | | 4/3(3r-6)=12 | | 5.5-x=-4-x | | -133+8x+6x=77 | | -7(-4n-1)=208 | | 3(m-6)-4m=-10 | | 2/9(4a+18)=4 | | 710-35x=290+25x | | -15+4m=-11m | | 12=5m-23+2m | | 10(d+5)=7(d+2) | | f-15=4f-3 | | 3(q+4)=3q=11 | | -4b-6=-10-2b | | 4b+3=7b-9 | | 17=6x+1-4 | | 1/9(4a+49)=-7 | | -6.5=1.3n | | -0.25(x+2)+5=-x | | -121b=-424 | | 5(x+9)+16=18 | | 3g-3=3(3-g) | | B=5/2(j-71) | | 3(d-6)=56 | | 8-(6-8x)=4x+2 | | 3x-2/3=4/5 | | 70x-10=0 | | 4(f/5-2)=20 | | -r+3=-3-3r+2r | | -4(r+7)=-62 | | 3(q+4)=3q+11 | | 6x−11=43 |